(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The study was carried out to assess leadership in geo –technical engineering in USA and its effectiveness in the management of deep foundation testing project and the challenges. In this study, an Ex Post Facto design was adopted. The study was carried out in USA. The targeted population for the study comprised civil engineers, project manager and project management consultants in USA. A stratified random sampling technique was used to select 10 respondents from 6 different types of geo-technical engineering services in USA such as Foundation Engineering, Earthquake Engineering, Geo-environmental Engineering, Geo-technical Hazard Mitigation, Geo-technical Instrumentation and Monitoring as well as Geo-synthetics and Geo-technical Materials. This was done by selecting 8 civil engineers, 1 project manager and 1 project management consultants which gave a total of 60 respondents used for the study. A stratified random sampling technique was used to select 10 respondents from 6 different types of geo-technical engineering in USA. The instrument used for data collection was a structured questionnaire titled “Deep Foundation Testing Leadership Project Questionnaire (DFTLPQ)”. Face and content validation of the instrument was carried out by an expert in project management and one expert in quantitative analysis in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.85, and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical technique such as a descriptive statistical analysis (percentage analysis). The study found out that Clear Vision and Direction” with the frequency of 37(12) and percentage of 19.68 was rated as the highest effects of leadership in geo-technical engineering on effective management of foundation testing. It was also observed that the greatest challenge faced by Geo-Technical Engineering Companies in their operations in USA is “Site and Soil Variability” with the frequency of 39(12) and the percentage of 20. Finally, there is significant effect of leadership in geo-technical engineering on effective management of foundation testing in USA at 0.05 alpha level with 58 degree of freedom (calculated as 0.90 and R-critical as 0.214. One of the recommendations made was that leaders should encourage their team members to pursue certifications, attend relevant workshops and conferences, and encourage continuous education and training in the latest geo-technical engineering techniques and technologies.